PF-29 Worms Infestation in Stray Cats at North Bogor - Risa Tiuria; Tetty Barunawati Siagian (Hemera Zoa, 2018)
Stray cats population are high in Indonesia, including in North Bogor area which is a part of Bogor City. North Bogor is the fourth largest area of 6 districts in the city of Bogor. North Bogor are an area of industrial with a lot of factories and housing. This vast area of North Bogor is a suitable place to live for stray cats. Stray cats can easy to breed and adapt in any environment. This is some of the factors in the increasing population of stray cats in North Bogor. Stray cats have a high interaction human life. The existence of this stray cats has the potential to cause zoonotic disease for humans. One of the problems caused by stray cats is the presence of zoonotic parasitic worms. Stray cats have the potential for occurrence of worm infections [1]. Research on zoonotic worm infections in stray cats is still rarely performed in Indonesia when compared to domesticated cats [2,3,4]. Specific worm infection studies such as Toxocara cati have been done in pet cats in Bogor city [5] and in Denpasar City, Bali [2,3] but have not been done to stray cats in the City of Bogor. For that it requires more studies on infection of worms in stray cats in the city of Bogor. This study aims to identify worms in stray cats in the area of North Bogor.